Risk of Cardiovascular Diseases and Cancer in Later Life: The Role of Age at First Marriage - Hui Liu; Zhenmei Zhang; Seung-won Choi (Geriatrics, 2018)
The objective of this study was to examine how age at first marriage is related to the risk of developing cardiovascular diseases and cancer in later life. We analyzed longitudinal data from a nationally representative sample of 2129 older adults (born in the 1940s or earlier) in the National Social Life, Health, and Aging Project. We found that for men in this cohort, the age at first marriage that was related to the lowest risk of cardiovascular diseases (CVD) and cancer in later life was the early 30s; men who first married at either younger or older ages had significantly higher odds of experiencing CVD and cancer. Interestingly, for women in this cohort, the age at first marriage was not related to the risk of either CVD or cancer.